2008
DOI: 10.5784/24-2-64
|View full text |Cite
|
Sign up to set email alerts
|

The identification of possible future provincial boundaries for South Africa based on an intramax analysis of journey-to-work data

Abstract: National census data contain information on place of residence and place of work. It is possible to combine this information and create journey-to-work flows. The process of establishing these flows are presented in this paper. The intramax method is explained and used to identify functional regions based upon these flows. Interesting applications, such as the demarcation of regions in South Africa are considered and solutions to disputed areas are put forward. The process of the creation of the current provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…From these flows interesting applications, such as the demarcation of regions in South Africa and solutions to disputed areas can be determined. The paper by Nel et al (2008) also showed how this method can be used to propose new boundaries for four or five new provinces.…”
Section: Local Governmentmentioning
confidence: 99%
“…From these flows interesting applications, such as the demarcation of regions in South Africa and solutions to disputed areas can be determined. The paper by Nel et al (2008) also showed how this method can be used to propose new boundaries for four or five new provinces.…”
Section: Local Governmentmentioning
confidence: 99%
“…This new FR now takes the place of the two parent BDUs/FRs in the the analysis. Thus, with  basic data units, all BDUs are grouped together into one FR after  − 1 interactions become intrazonal (Brown and Pitfield, 1990;Masser and Brown, 1975;Masser and , 1980;Nel et al, 2008). The procedure, as well as the results of the hierarchical aggregation, can in a tree structure of a dendrogram.…”
Section: Development and Implementation Of The Intramax Methodsmentioning
confidence: 99%
“…In its relative simplicity and its implementation in publicly available software 4 , however, one sees the reason that the Intramax method has been used so many times to analyse FRs -of so many different kinds of interactions at very different levels of consideration, for example: labour market area delineation (Masser and Scheurwater, 1980;Feldman et al, 2005;Watts, 2009;Landré, 2012;Landré and Håkansson, 2013;Koo, 2012); housing market area delineation (Goetgeluk and de Jong, 2007;Brown and Hincks, 2008;Jaegal, 2013); commodity market delineation (Brown and Pitfield, 1990); world trade block delineation (Poon, 1997;Kohl and Brouver, 2014); functional economic region delineation (Mitchell et al, 2007(Mitchell et al, , 2013Mitchell and Stimson, 2010;Mitchell and Watts, 2010); telecommunication analysis (Fischer et al, 1993); to identify possible administrative or statistical regions (Nel et al, 2008;Bogataj, 2012a, 2012b); transport regions (Krygsman et al, 2009); in the (allocation) analysis of services Bogataj, 2014, 2015), and so forth.…”
Section: Development and Implementation Of The Intramax Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method builds upon Ward's (1963) hierarchical clustering procedure, which is adjusted for interaction data. The Intramax approach was applied by Nel et al (2008), Drobne and Bogataj (2012), and Landré (2012) relatively recently.…”
Section: Tab 1: Classification Of Approaches To a Functional Regionamentioning
confidence: 99%